2016
DOI: 10.1080/15384101.2016.1154245
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the uL11 protein impact on translational machinery

Abstract: The ribosomal GTPase associated center constitutes the ribosomal area, which is the landing platform for translational GTPases and stimulates their hydrolytic activity. The ribosomal stalk represents a landmark structure in this center, and in eukaryotes is composed of uL11, uL10 and P1/P2 proteins. The modus operandi of the uL11 protein has not been exhaustively studied in vivo neither in prokaryotic nor in eukaryotic cells. Using a yeast model, we have brought functional insight into the translational appara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 69 publications
(86 reference statements)
1
28
0
Order By: Relevance
“…variants. Our findings also corroborate observations in yeast that RPL12 deletion slows translation (11,12) and complement these data with the discovery that the overall effect is global, albeit dependent on the specific protein defect and/or codon context. For what we believe is the first time, we used this approach to establish impact of disease-relevant mutations on CFTR biogenesis from a mechanistic perspective, including effects on elongation.…”
Section: Figure 3 Silencing Rpl12 Enhances F508del-cftr Functional Esupporting
confidence: 90%
“…variants. Our findings also corroborate observations in yeast that RPL12 deletion slows translation (11,12) and complement these data with the discovery that the overall effect is global, albeit dependent on the specific protein defect and/or codon context. For what we believe is the first time, we used this approach to establish impact of disease-relevant mutations on CFTR biogenesis from a mechanistic perspective, including effects on elongation.…”
Section: Figure 3 Silencing Rpl12 Enhances F508del-cftr Functional Esupporting
confidence: 90%
“…In such a situation, EF-2-catalyzed translocation should be affected to the same extent as decoding, because elongation consumes equal numbers of eEF-2-and eEF-1A-dependent steps. Interestingly, such a situation was indeed described for uL11-depleted yeast cells (64). Since uL11 is present on the ribosome in a single copy, ribosomes lacking this protein were equally defective in all trGTPase dependent steps, including ribosome biogenesis, subunit joining, translation elongation, and termination, and especially affecting central ribosomal activity, the elongation cycle, which was depicted as perturbations in misincorporation, and Ϫ1 and ϩ1 PRF (64).…”
Section: P1/p2 Proteins Are Dispensable For the Translational Speed Imentioning
confidence: 80%
“…It has been shown that the stable association of Yvh1 with pre-60S r-particles depends on the r-protein L12 (uL11), which is the closest neighbour of P0 at the base of the P-stalk 4447. However, still in the absence of L12, there is apparently no difference in the efficiency of Mrt4 re-importation to the nucleus (48, and our unpublished results). In conclusion, despite the fact that yeast Mrt4 and Yvh1 are non-essential proteins under standard laboratory conditions, both factors may play important roles controlling the position and timing of the assembly of P0, simultaneously providing a surveillance point to ensure that only mature LSUs can engage in translation (see below; further discussed in 141720).…”
Section: The Classical View: Paralogues Of Ribosomal Proteinsmentioning
confidence: 67%